Assessing Fatigability in Mobility-Intact Older Adults - Simonsick, Eleanor M. (2014)
OBJECTIVES: Evaluate criterion validity of two measures of fatigability defined as performance deterioration or perceived effort to perform a standardized task. DESIGN: Cross-sectional analysis of data from the Baltimore Longitudinal Study of Aging (BLSA). SETTING: National Institute on Aging, Intramural Research Program, Clinical Research Unit, Baltimore, Maryland. PARTICIPANTS: Six hundred five men (53.7%) and women (aged 65–97) participating in the BLSA eligible for endurance walk testing without a walking aid. MEASUREMENTS: Fatigability was assessed using (1) completion status and lap times from a 400m-walk performed “as quickly as possible” and (2) perceived exertion rating using the Borg scale (range 6–20) following 5 minutes of treadmill walking at 1.5mph (0.67m/s). Criterion measures include self-report of tiredness, level of weakness and energy in past month and walking ability and objective measures of usual and fast gait speed, time to complete 10 chair stands and grip strength. Co-variates include age, race, sex, obesity, smoking status and walking activity. RESULTS: Among mobility intact older persons, 23% exhibited performance deterioration (i.e., slowed or stopped) during the 400m-walk and1/3 reported more than very light exertion following a 5-minute slow walk. Slowing was strongly associated with self-reported fatigue and walking ability, but weakly associated with performance-based mobility measures. High perceived exertion was associated with tiredness and weakness and reported and observed mobility deficits. CONCLUSION: Slowing down may have low sensitivity for identifying fatigability in older persons, but ascertaining perceived exertion during a defined workload shows promise. In seemingly healthy, motivated individuals, fatigue and fatigability were common and may impact socially meaningful mobility behaviors. Assessment of fatigability in well-elderly examinations may help identify threats to independent functioning earlier in the decline process.